The role of theragnostics in oncology: an interview with Stefano Buono - Buono, Stefano (International journal of endocrine oncology, 2017)
Stefano Buono is the Chief Executive Officer, a member of the board of directors, and a founder of Advanced Accelerator Applications (AAA). He has been responsible for overseeing AAA operations, including the development and commercialization of the current portfolio of diagnostic and therapeutic molecular nuclear medicine products, and listing AAA on Nasdaq (stock symbol: AAAP). Prior to founding the company in 2002, he worked as a physicist at the Centre for Advanced Studies, Research and Development, or CRS4, in Italy. During his 6-year tenure with CRS4, he headed a team of engineers working on different international research projects in the field of energy production and nuclear waste transmutation. Before working at CRS4, and alongside his appointment at CRS4, he worked with Physics Nobel Laureate Carlo Rubbia at The European Organization for Nuclear Research (CERN), the world's largest research laboratory for particle physics, in Geneva, Switzerland. He actively participated in the development of CERN's Adiabatic Resonance Crossing (ARC) method. He is the author of numerous scientific papers. He received his Master's degree in Physics from the University of Turin, in Italy, in 1991.